Ablative behavior and mechanism of SiCf/SiBCZr composites prepared by PIP process - Mingwei Chen; Yuliang Zhao; Haipeng Qiu; Shijian Liu; Weijie Xie; Yi Chen; Qiyue Zhang (Journal of Advanced Ceramics, 2024)
SiCf/SiBCZr composites were prepared by polymer precursor impregnation and pyrolysis process with near stoichiometric ratio SiC fiber preform as reinforcement phase and SiBCZr multiphase ceramic precursor as impregnating reagent. The results highlighted that the SiCf/SiBCZr composites exhibited excellent ablative properties after ablative tests at 1200 ℃/3600 s and 1400 ℃/3600 s, and the strength retention rates of the composites reached 90% and 85%, respectively. This was mainly due to the liquid sealing effect of the ablative products represented by B2O3 and SiO2∙B2O3, which inhibited the ablative reaction by reducing the diffusion rate of the oxidation medium, and the solid pinning effect of the substances represented by SiO2, ZrO2, and ZrSiO4, which could play high viscosity and high strength characteristics to improve anti-erosion ability. The above-mentioned SiCf/SiBCZr composites with corrosion resistance, oxidation resistance, and ablative resistance provided a solid material foundation and technical support for the development of reusable spacecraft hot-end components.